Evaluation Method for Tourism Development Focused on Poverty Alleviation - Simorangkir, Cavin Ornando; Sabrina Rahmadhanty Maghfira (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
This study aims to evaluate the effectiveness of tourism development in poverty alleviation, focusing on systems and policies implemented in Indonesia. Using a qualitative approach, document analysis was employed to review various policies, case studies, and strategies implemented in several countries/regions. The data used include scholarly articles, regulations, written policies, and notes from stakeholders relevant to tourism development and poverty alleviation. The document analysis results indicate that pro-poor tourism development policies require a holistic and contextual evaluation, considering local conditions, social capital, and impact mapping. This study also explains relevant and contextual evaluation methods for pro-poor tourism related to regional development policies, including evaluation of policy formulation, implementation, and development outcomes. Thus, this research is expected to make a significant contribution to expanding the understanding of tourism development evaluation focused on poverty alleviation and to provide more effective and targeted policy recommendations.